Relationship between Vitamin D Deficiency, Diabetes, and Obesity. Issue 2 (March 2019) - Alloubani, Aladeen; Akhu-Zaheya, Laila; Samara, Rama; Abdulhafiz, Ibrahim; Saleh, Abdulmoneam; Altowijri, Albaraa
Abstract: Aim: This study aimed to assess the prevalence of VDD in Saudi Arabia, revealing the lifestyle and nutritional habits; and assesses the association between VDD, Diabetes Mellitus, and obesity. Methods: A descriptive, cross-sectional, and correlational design was used in this study. A convenience sampling method of 350 participants participated in the study. Results: The results revealed that the probability of having vitamin D Deficiency was higher among females (OR = 2.06, p  > .05); younger age-whereby with each one year decrease in age there was about 0.03 probability of having Vitamin D Deficiency (B = −0.03; p  > .05); individuals with higher incomes (OR = 1.44, p  > .05); smokers (OR = 0.08, p  > .05); and a lack of exposure to the sun (OR = 8.50; p  > .05). In addition, exercise is also a predictor of Vitamin D deficiency (OR = 3.8; p  > .05). Moreover, less Vitamin D intake (OR 9.7; p  > .05), less intake of Calcium (OR = 12.2, p  > .05); In addition increase one unit in the BMI, cholesterol, LDL, HDL, and FBS increased the log odd of having liability of Vitamin D deficiency by 3.2; 1.9, 1.8, 1.0, and 2.4 ( p  > .05). Conclusion: Vitamin D Deficiency was prevalent in both males and females across different age groups in the citizens of Saudi. Because of the connection between Vitamin D Deficiency and main chronic disease, it is necessary to emphasize the need to recognize Vitamin D Deficiency screening for risk factors. It may be reasonable for the nutritionists, nurses, and physicians, to encourage the community on approaches to enhance dietary Vitamin D or suggest supplementation.